Reseña de: Capitalism in the Web of Life: Ecology and Accumulation of Capital (Moore, 2015) (2017)
Jason Moore. 2015. Capitalism in the Web of Life. Ecology and Accumulation of Capital [Capitalismo en la red de la vida. Ecología y acumulación de capital]. London New York: Verso Books. 336 pp. ISBN 978-1781689028.